ANTICANCER, CYTOTOXIC EFFECT OF TAMARIX APHYLLA, AND ANTIBACTERIAL SCREENING EFFICIENCY AGAINST MULTIDRUG-RESISTANT HUMAN PATHOGENS - Al Sobeai, Sanad M (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present study aimed to investigate the anticancer, cytotoxic effect of Tamarix aphylla, and antibacterial effectiveness against 10 pathogenic bacteria that cause common and sometimes serious infections in human and animals. Methods: T. aphylla fresh and disease-free leaves were collected from the different geographical regions of Saudi Arabia. The anticancer, cytotoxic effect of T. aphylla leaves, and antibacterial screening efficiency against multidrug-resistant human pathogens were investigated in vitro using Vero cells as a normal cells and MCF-7 (breast adenocarcinoma cells). Results: T. aphylla leaf extracts exhibited a low cytotoxic effect on Vero cell line at high concentration, with an 50% cytotoxicity concentration value of >1000 Î¼g/ml. The methanolic extract inhibited MCF-7 cancer cells in a concentration-dependent manner. The methanol and ethanol extracts showed antibacterial activity with variable inhibition effects and differences in their activities against tested pathogenic bacteria ranging from very high inhibition (20.7Â±1.3 mm) to low (4Â±0.6 mm). The minimum inhibitory concentration of methanol and ethanol results showed no significant differences. Conclusions: The findings of this study conclude that the T. aphylla leaf extract had lower toxicity on normal cell line (low toxic plant) and significantly inhibited the growth of cancer cells. T. aphylla has potential antibacterial biomolecules against multidrug-resistant human pathogens.